2012
DOI: 10.1093/hmg/dds465
|View full text |Cite
|
Sign up to set email alerts
|

The molecular function and clinical phenotype of partial deletions of the IGF2/H19 imprinting control region depends on the spatial arrangement of the remaining CTCF-binding sites

Abstract: At chromosome 11p15.5, the imprinting centre 1 (IC1) controls the parent of origin-specific expression of the IGF2 and H19 genes. The 5 kb IC1 region contains multiple target sites (CTS) for the zinc-finger protein CTCF, whose binding on the maternal chromosome prevents the activation of IGF2 and allows that of H19 by common enhancers. CTCF binding helps maintaining the maternal IC1 methylation-free, whereas on the paternal chromosome gamete-inherited DNA methylation inhibits CTCF interaction and enhancer-bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 31 publications
2
96
0
Order By: Relevance
“…Determining the extent to which these mutations contribute to the molecular and clinical phenotypes of BWS is challenging, because IC1 hypermethylation is mosaic in the patients, suggesting that not all cells are aberrantly DNA-methylated. Moreover, clinical phenotypes of the patients are highly variable, possibly as a consequence of either the mosaicism or the genetic background of the individuals (27). In this study, we have shown that maternal transmission of hIC1 can functionally replace mIC1 by properly regulating imprinted expression and hIC1 methylation.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Determining the extent to which these mutations contribute to the molecular and clinical phenotypes of BWS is challenging, because IC1 hypermethylation is mosaic in the patients, suggesting that not all cells are aberrantly DNA-methylated. Moreover, clinical phenotypes of the patients are highly variable, possibly as a consequence of either the mosaicism or the genetic background of the individuals (27). In this study, we have shown that maternal transmission of hIC1 can functionally replace mIC1 by properly regulating imprinted expression and hIC1 methylation.…”
Section: Resultsmentioning
confidence: 63%
“…Several groups have reported that a subset of patients with BWS carry mutations at IC1, and that these mutations are largely associated with IC1 hypermethylation, reduced H19 expression, and biallelic Igf2 expression. Notably, these IC1 mutations (i.e., microdeletions and point mutations) manifest BWS clinical phenotypes when the mutant allele is maternal in origin (9,27,28). Determining the extent to which these mutations contribute to the molecular and clinical phenotypes of BWS is challenging, because IC1 hypermethylation is mosaic in the patients, suggesting that not all cells are aberrantly DNA-methylated.…”
Section: Resultsmentioning
confidence: 99%
“…In particular in the 11p15-associated disorders (BWS and SRS), nearly all patients with epimutations and UPD show mosaicism (for review: [13]). As a consequence of mosaicism, the molecular alterations currently often escape diagnostic detection in case of a low level mosaicism [30], an unequal distribution in different tissues [15], or an insufficient sensitivity of assays [31,32]. New diagnostic approaches therefore may analyze different tissues from the same patient as well as apply multilocus and/or deep-sequencing tests.…”
Section: Translational Use Of New Techniques In Idsmentioning
confidence: 99%
“…For the same purposes, deep-sequencing NGS assays have been developed, and it has been shown that this technique is able to detect even low-level mosaicism [31,32]. As it is generally observed for genetic testing, NGS will also improve the diagnostic workup in imprinting disorders, even in so far unexpected fields like non-invasive prenatal testing [35].…”
Section: Translational Use Of New Techniques In Idsmentioning
confidence: 99%
“…ICR2 hypomethylation 50-60% UPD(11p15)pat 20-25% CDKN1C point mutations 3,4 1.3-5% in sporadic cases, 20-40% in familial cases Duplication of paternal chromosome 11p15.5 1-2% ICR1 microdeletions (for review 5 ) o1%…”
Section: Icr1 Hypermethylation 5-10%mentioning
confidence: 99%